Strangeness Concept in Commercial Advertisement Design: يوسف مهدي سعيد -سحر علي سرحان (Al-Academy, 2020)
Strangeness in design generally and in advertisement design specifically is manifested in various images and creative propositions and shapes that depart the traditional and conventional framework to elevate design to virtual intellectual worlds related to the inspirational and imaginative range of the creative designer, which makes the forms of strangeness a means for persuasion and astonishment which achieves the functional and aesthetic objectives of the advertisement. The two researchers identified the research question "what is the concept of strangeness in the commercial advertisements design? The research objective has been determined by identifying the concept of strangeness in the commercial advertisement design. Strangeness has been employed as a term for the research, which has been tackled in the first chapter. The second chapter has been dedicated for the theoretical framework including topics tackled in the first chapter such as the concept of strangeness in art, the concept of strangeness in design. The second section also included the advertisement production and strangeness. As for the third chapter, it addressed the research procedures and the analysis of a number of samples of a set of commercial advertisements of Pepsi Cola Company, for the Pepsi cola carbonated drink produced by PepsiCo International Company from 2014-2018. The number of samples of the research community after the survey done by the two researchers in the relevant locations has been (12) commercial advertisements. The research samples have been chosen in an intentional non-probability method being (3) samples constituting 25% of the research community.